1994
DOI: 10.1002/jcp.1041580322
|View full text |Cite
|
Sign up to set email alerts
|

Cellular expression of bone‐related proteins during in vitro osteogenesis in rat bone marrow stromal cell cultures

Abstract: Rat bone marrow stromal cells comprise a heterogeneous mixture of cell lineages including osteoblastic cells. When grown in the presence of ascorbic acid, beta-glycerophosphate and 10(-8) M dexamethasone, osteoprogenitor cells within the population divide and differentiate to form bone nodules (Maniatopoulos et al., 1988, Cell Tissue Res., 254:317-330; Aubin et al., 1990, J. Bone Miner. Res., 5:S81) providing a useful model to investigate temporal and spatial changes in expression of osteoblastic markers. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
214
2
6

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 342 publications
(245 citation statements)
references
References 68 publications
23
214
2
6
Order By: Relevance
“…OC is another late bone marker only secreted by osteoblasts [20] and also signals terminal osteoblast differentiation [7]. OC was not found in any cultures at four and seven days.…”
Section: Discussionmentioning
confidence: 93%
“…OC is another late bone marker only secreted by osteoblasts [20] and also signals terminal osteoblast differentiation [7]. OC was not found in any cultures at four and seven days.…”
Section: Discussionmentioning
confidence: 93%
“…Identifying a relationship between population growth, nodule formation, and expression of surface or other osteoblast markers is the object of much study [15,16,28,[49][50][51][52]. To this end, separation of the input RC population into four purified fractions (ALP showed that nodules are able to form within each fraction [53].…”
Section: Of Mineralized Nodules After 21 Days In Vehicle (Hatched) Ormentioning
confidence: 99%
“…CA) and the area of nodules was measured using Sigmascan software (Jandel Corporation, San Rafael, CA). The number of nodules was counted in all groups with four patients in each [30][31][32][33][34][35][36][37][38] group and two separate experiments (with different subjects) were performed.…”
Section: Hisfon~or~/iar?zefr~mentioning
confidence: 99%
“…After cells reach confluence, nodules of multilayered osteoblasts form in scattered foci. The nodules stain for alkaline phosphatase [4,42], and are the regions where bone extracellular matrix proteins are deposited [36] and mineralization occurs. Previous studies have shown that the mineralized nodules resemble woven bone that is produced in vivo [4,8,13,20,42].…”
Section: Expression Of Mrna Levels For Hone Matrix Proteins and Ininementioning
confidence: 99%